Pediatric Nephrolithiasis: A Changing Landscape Through Time and Space - Luca Pecoraro; Arianna Zuccato; Rebecca Vitella; Angelo Pietrobelli; Giorgio Piacentini; Milena Brugnara (Medicina)
Pediatric nephrolithiasis is an ancient and complex disorder that has seen a significant rise in recent decades and the underlying causes contributing to stone formation in children may also be shifting. Historically, kidney stones have been linked to factors such as metabolic disorders, congenital abnormalities, and family history. However, the recent increase in incidence appears to be associated with new risk factors, including changes in lifestyle and diet, the growing prevalence of obesity, metabolic syndrome, diabetes, and even climate change. Given this evolving landscape, performing a comprehensive metabolic evaluation during the diagnostic process is essential. A complete metabolic evaluation should thus be performed during the diagnostic assessment to identify any modifiable risk factors predisposing to stone recurrence and reduce the need for surgical management, extrarenal comorbidity, and the increased burden of care.